DAMPAK ERUPSI MERAPI TERHADAP PENDAPATAN PETANI SALAK NGLUMUT DI DESA KALIURANG KECAMATAN SRUMBUNG KABUPATEN MAGELANG TAHUN 2009-2011 - Trisni Wulandari (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2014)
This research aims to know the impact of the eruption of Merapi to the income of farmers in nglumut village of Kaliurang bark town in Srumbung Magelang Regency in 2009-2011. The technique of data collection method using proporsional area random sampling The Data used are the result of productivity, data production, costs of production, farmers ’ income before and after the eruption of Merapi occurred. Analysis of the significant difference test is used to see the difference in productivity before and after the eruption of Merapi occurred of data is done with the analysis of R/C ratio to see comparison of farming income. Research results through different trials showed significant t value amounted to 5,399 > t-table of 1,6782 (with df 49 and confidence level of 95%) and a significant degree of probability on the Sig (2-tailed) = 000 therefore H0 denied that shows there are indeed differences in the productivity of the bark nglumut before and after the eruption of Merapi occurred. Nglumut bark productivity before the eruption of 3960 Kg/year and after eruptions occur 3840 Kg/year. A comparison of total revenues with total costs to farming bark Volcano Eruptions before the nglumut get R/C amounted to 2.72 while for after the eruption had R/C 1.73.